1999
DOI: 10.1098/rspb.1999.0635
|View full text |Cite
|
Sign up to set email alerts
|

Kin recognition in a social spider

Abstract: Social spiders accept immigrant spiders into their kin-based groups, suggesting that spiders cannot recognize kin and may lose inclusive ¢tness bene¢ts. A ¢eld and two laboratory experiments on Diaea ergandros, a social crab spider, demonstrated that younger and older instar D. ergandros do discriminate siblings, but potential bene¢ts were variable and not equally distributed. First, proportional survival was greater in large groups regardless of the within-group relatedness, so accepting immigrants increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 29 publications
2
62
1
Order By: Relevance
“…These cues might be intraspecific chemical odours, which have direct or indirect genetic foundations (Roberts et al, 2003). Chemically mediated kin recognition is reported in spiders (Miller, 1989;Evans, 1999). Cannibalism did not occur more or less frequently when the larvae were fed the same diet compared to different diets, suggesting that diet has no role as an exogenous cue for detecting kinship.…”
Section: Discussionmentioning
confidence: 99%
“…These cues might be intraspecific chemical odours, which have direct or indirect genetic foundations (Roberts et al, 2003). Chemically mediated kin recognition is reported in spiders (Miller, 1989;Evans, 1999). Cannibalism did not occur more or less frequently when the larvae were fed the same diet compared to different diets, suggesting that diet has no role as an exogenous cue for detecting kinship.…”
Section: Discussionmentioning
confidence: 99%
“…As many taxonomic groups have not been studied (Table 7.1), general conclusions about the occurrence and adaptive significance of kin recognition cannot be drawn. However, based on the present data its benefits seem to be unequally distributed across the taxon and often not easy to reveal (Evans 1999). It is important to note that the apparent lack of kin discrimination does not necessarily imply that this trait is absent; it may simply not be in use in relation to the behaviours under investigation.…”
Section: Intraspecific Discrimination and Kin Recognitionmentioning
confidence: 76%
“…In the thomisid subsocial spider Diaea ergandros, Evans (1999) showed that the performance of sibling groups does not significantly differ from groups of unrelated individuals in the adult stage. Juveniles, however, contribute more to nest construction when cooperating with siblings, and if unfavourable conditions causes the colony to starve, cannibalism spreads and spiders then prefer to eat non-sibs first (Evans 1999).…”
Section: Kin Recognition In Subsocial Spidersmentioning
confidence: 98%
“…The filial cannibalism and nest mate recognition in F. binodulus resembles that in social spiders in which sociality is associated with a family group and extended maternal care. Although unrelated spiders are accepted by a group, cannibalism and some kin recognition occurs (Evans, 1999). In addition, communal breeding is often profitable even if group members are not kin.…”
Section: Discussionmentioning
confidence: 99%